An Intellectually Humbling Experience: Changes in Interpersonal Perception and Cultural Reasoning across a Five-Week Course. Issue 3 (September 2019) - Meagher, Benjamin R.; Gunn, Hanna; Sheff, Nathan; Van Tongeren, Daryl R.
Finding ways to foster intellectual humility (IH)—the willingness to own one's limitations—is an important goal for facilitating effective learning. We report the results of a longitudinal, quasi-experimental study, conducted across six undergraduate, culturally diverse (58% racial/ethnic minority) introductory philosophy courses, that evaluates how social perceptions and cross-cultural reasoning change following a course on epistemology and social ethics. Critically, we manipulated whether each class received a standardized lesson in IH at the start of the course or not. Participants provided self-ratings of IH, gave round-robin judgments of their classmates, and completed a wise-reasoning writing exercise focusing on a cultural conflict at both the beginning and end of the summer course session. Results revealed no change in self-reported IH, but an increase in perceived peer IH and conscientiousness within classes where IH was taught. Moreover, an analysis of the participants' writing suggested greater levels of compromise-seeking when dealing with a cultural conflict among the students taught about IH, relative to those in the control classes. This study provides initial insights regarding the relationship between IH and cultural humility, as well as the efficacy of facilitating the development of IH among undergraduate students.